2015
DOI: 10.1071/mf14316
|View full text |Cite
|
Sign up to set email alerts
|

Growth and spatiotemporal distribution of juvenile shortfin mako (Isurus oxyrinchus) in the western and central North Pacific

Abstract: This paper presents an estimation of growth curves and spatiotemporal distributions of juvenile shortfin mako shark (Isurus oxyrinchus) in the western and central North Pacific Ocean using port sampling data collected from 2005 to 2013. The monthly length compositions show a clear transition of three modes in the size range of smaller than 150-cm precaudal length (PCL), which were believed to represent the growth of age-0 to age-2 classes, and they were then decomposed into age groups by fitting a Gaussian mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
4
16
0
Order By: Relevance
“…The migration of age-0 and 1-year-old juveniles observed in our results could be related to the increase in SST during the year, which coincides with the findings reported by Kai et al (2015) in the North Pacific Ocean and western Pacific Ocean for the Shortfin Mako and which is related to the thermal preferences of this species. Another possibility is that juveniles may be migrating in response to the movement of smaller fish that serve as food and in turn seek the nutrient-rich waters of coastal upwellings, such as the California Current.…”
Section: Discussionsupporting
confidence: 80%
“…The migration of age-0 and 1-year-old juveniles observed in our results could be related to the increase in SST during the year, which coincides with the findings reported by Kai et al (2015) in the North Pacific Ocean and western Pacific Ocean for the Shortfin Mako and which is related to the thermal preferences of this species. Another possibility is that juveniles may be migrating in response to the movement of smaller fish that serve as food and in turn seek the nutrient-rich waters of coastal upwellings, such as the California Current.…”
Section: Discussionsupporting
confidence: 80%
“…Comparison of the length frequencies from these surveys with the reported growth parameters of North Pacific blue shark (Nakano, ) and shortfin mako (Semba et al ., ; Wells et al ., ; Kai et al ., ) indicated that both species caught in the surveys ranged from the young‐of‐the‐year class to young adults. In particular, shortfin mako showed an apparent mode at a precaudal length of around 70 cm, which is close to its recruitment size (Semba et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The age and growth of the shortfin mako Isurus oxyrinchus Rafinesque 1810 has been studied since the early 1980s (Cailliet & Bedford, ; Pratt & Casey, ; Francis & Duffy, ; Ardizzone et al , ; Bishop et al , ; Natanson et al , ; Cerna & Licandeo, ; Semba et al , ; Wells et al , ; Doño et al , ; Kai et al , ). Several methods have been used in past studies including length‐frequency analysis and tag‐recapture growth, but the most common method for age determination has been counting alternating growth bands in vertebral centra.…”
Section: Distances Between Band Pairs and The Estimated Life Stage Bamentioning
confidence: 99%